Caracterização dos acidentes de trabalho grave em Uberaba – MG: compreensão de suas causas, atenção na rede SUS e impactos sobre condições de vida e trabalho - Trajano, Josiana Dias Silva (2017)
Occupational Accidents (AT) are complex and multi-causal and require in-depth investigation to identify the reasons for their occurrence. They pose a challenge to public health, since they have consequences for workers, families, communities and the country's health system and economy. The objective of this research is to characterize the workers who are victims of serious occupational accidents (ATG) in Uberaba, Minas Gerais, Brazil, in 2015, and to analyze how they understand the causes of accidents, the impacts on their life and work processes, and the attention health provided by the institutions. This is a descriptive and explanatory study with a quantitative-qualitative approach developed among workers who suffered from ATG and were attended by the CEREST Regional Uberaba worker health surveillance team. The documentary sources consulted were: 204 ATG records, from January 1 to December 31, 2015, and 104 ATG Research Reports. Sixteen workers gave interviews. Data obtained from documentary sources were analyzed using the quantitative methodology. The qualitative methodology led to the collection and thematic analysis of the interviews in which the following categories emerged: ATG, attention in the national health system and consequences of the work accident. The profile of the ATG victim was thus constituted: male (88%), white (48%), between 21 and 40 years old (58%). The main occupations are related to extractive production, industrial processes and civil construction (45%), standing out the masons (79%). The CAT was emitted in 74% of the cases. Accidents occur mainly at the contractor's premises (72%). The most frequent causes were transportation accidents, injuries, falls, exposure to mechanical forces and exposure to electric current (64%). Health care was performed in hospitals (65%) and UPAs (29%). The most frequent case evolution was temporary incapacity (81%).he qualitative dimension of the study evidenced that the workers victims of ATG emphasize as causality of the accident the fatality, bad luck and they blame themselves. They rarely cite working conditions. Regarding the conditions of the working environment, the use of personal protective equipment, work tools, type of work performed and training were verified. Although they describe the tools and working conditions, the interviewees do not relate them to the accident. Assistance in the National Health Network was studied considering the care received and its evaluation. Efforts were made by the professionals of the institutions to relate the accident to work and provide guidance. The first care was well evaluated and there were reports of difficulties to access the specialized care. The ATG developments focused on the study on access to labor rights, impacts on work and impacts on the health of the worker and the family. The testimonies reinforce the need for changes that lead to the adoption of protective measures that bring more safety in the execution of the work. It is up to CEREST and other institutions of the National Health Network to broaden the approach of the injured worker in order to guarantee integral attention, including in labor matters.